Simulation and analysis of user-side transaction technology for energy blockchain considering multi-chain structure. (26th March 2020) - Zheng, Guping; Hu, Jingya; Li, Gang
Blockchain advantages, such as decentralised tamper-proof and smart contracts, are naturally suitable for the trading needs of energy internet, dealing with the problems of low efficiency, waste of resources, privacy leakage, etc. In this paper, an energy trading method is proposed based on blockchain expansion technology. The lightning network is used to expand the blockchain trading process, and divides the transaction into on-chain trading and off-chain trading; and the chain structure of the energy blockchain is expanded using a multi-chain architecture, and the blockchain is divided into an account blockchain and a transaction blockchain. A case study is carried out, in this research work, in combination with multiple energy trading scenarios in the energy local area network (LAN). The results show that the proposed method possesses a significant performance of improving the efficiency of energy trading and reducing the complexity of trading information.